2018
DOI: 10.1007/978-3-030-01168-0_9
|View full text |Cite
|
Sign up to set email alerts
|

State of the Art Literature Review on Network Anomaly Detection

Abstract: As network attacks are evolving along with extreme growth in the amount of data that is present in networks, there is a significant need for faster and more effective anomaly detection methods. Even though current systems perform well when identifying known attacks, previously unknown attacks are still difficult to identify under occurrence. To emphasize, attacks that might have more than one ongoing attack vectors in one network at the same time, or also known as APT (Advanced Persistent Threat) attack, may b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
1
1
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…To detect these complex attacks, there are few issues that must be considered: i) dimension reduction and overlapping information may cause outliers to vanish and ii) taking into account earlier detected outliers from historical data. Our earlier research results [22,23] showed that deep learning methods have a high potential to resolve the considerations i) and ii). One concern is to locate sufficient amount of good quality network data, for executing training and benchmarking tests.…”
Section: Discussionmentioning
confidence: 97%
“…To detect these complex attacks, there are few issues that must be considered: i) dimension reduction and overlapping information may cause outliers to vanish and ii) taking into account earlier detected outliers from historical data. Our earlier research results [22,23] showed that deep learning methods have a high potential to resolve the considerations i) and ii). One concern is to locate sufficient amount of good quality network data, for executing training and benchmarking tests.…”
Section: Discussionmentioning
confidence: 97%
“…Current anomaly detection research [4,5] relies on similar methods, where outdated and heavily manipulated datasets, such as KDD98, KDDCUP99 and NSLKDD [6], are used for benchmarking proposed methods. Another issue is that complex problems are solved in a simple manner, that is, one type of method is used for handling the entire problem, such as one type or Machine Learning (ML) or Deep Learning (DL) algorithm.…”
Section: Current Detection Problemsmentioning
confidence: 99%